2000
DOI: 10.1021/jm9911027
|View full text |Cite
|
Sign up to set email alerts
|

Antimalarial Activity of Compounds Interfering with Plasmodium falciparum Phospholipid Metabolism: Comparison between Mono- and Bisquaternary Ammonium Salts

Abstract: On the basis of a previous structure-activity relationship study, we identified some essential parameters, e.g. electronegativity and lipophilicity, required for polar head analogues to inhibit Plasmodium falciparum phospholipid metabolism, leading to parasite death. To improve the in vitro antimalarial activity, 36 cationic choline analogues consisting of mono-, bis-, and triquaternary ammonium salts with distinct substituents of increasing lipophilicity were synthesized. For monoquaternary ammonium salts, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
118
0
3

Year Published

2003
2003
2011
2011

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(122 citation statements)
references
References 21 publications
1
118
0
3
Order By: Relevance
“…We have focused on mono-and bisquaternary ammonium compounds for their potent antimalarial activity in vitro and in vivo (6,7). These compounds mimic choline structure; they potently inhibit the low-affinity choline carrier related to phospholipid biosynthesis in eukaryotic cells and the high-affinity carrier involved in biosynthesis of the neurotransmitter acetylcholine in the CNS (8,9).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We have focused on mono-and bisquaternary ammonium compounds for their potent antimalarial activity in vitro and in vivo (6,7). These compounds mimic choline structure; they potently inhibit the low-affinity choline carrier related to phospholipid biosynthesis in eukaryotic cells and the high-affinity carrier involved in biosynthesis of the neurotransmitter acetylcholine in the CNS (8,9).…”
mentioning
confidence: 99%
“…G25 [1,16-hexadecamethylenebis(N-methylpyrrolidinium) dibromide] and other drugs in this class possess a permanently charged cationic group (7,13) that is essential for activity but detrimental to oral absorption. This action prejudiced development for the clinic.…”
mentioning
confidence: 99%
“…15) Calas et al have also demonstrated that interference with de novo PC biosynthesis by bis(quaternary ammonium salts) was lethal to malaria parasites, including chloroquine-resistant species (Scheme 1). 16) Therefore, if we combine these two components via covalent binding, the conjugate should have a different nature from the originals. For example, the solubility of the tetraoxane moiety in water may be significantly improved by the introduction of the ammonium ion.…”
mentioning
confidence: 99%
“…Compounds mimicking the structure of choline, a precursor required for phosphatidylcholine synthesis by the parasite, inhibit de novo phosphatidylcholine biosynthesis and are highly active against multiresistant P. falciparum malaria (3)(4)(5)(6)(7)(8)(9)(10). Three generations of compounds have been synthesized.…”
mentioning
confidence: 99%
“…Three generations of compounds have been synthesized. The first two consist of mono-or bisquaternary ammonium salts (6,7 ) and ami-dine and guanidine compounds, respectively. These compounds have outstanding efficacy both in vitro and in vivo against P. falciparum and P. cynomolgi, a P. vivaxrelated parasite, with a high therapeutic index (3 ).…”
mentioning
confidence: 99%